Acoustic Neurinoma with Synchronous Ipsilateral Cerebellopontine Angle Lipoma: A Case Report and Review of the Literature - Takahiro Kanaya; Yasuo Murai; Kanako Yui; Shun Sato; Akio Morita (Diagnostics, 2022)
Lipomas of the cerebellopontine angle (CPA) and internal auditory canal (IAC) are relatively rare tumors. Acoustic neurinoma is the most common tumor in this location, which often causes hearing loss, vertigo, and tinnitus. Occasionally, this tumor compresses the brainstem, prompting surgical resection. Lipomas in this area may cause symptoms similar to neurinoma. However, they are not considered for surgical treatment because their removal may result in several additional deficits. Conservative therapy and repeated magnetic resonance imaging examinations for CPA/IAC lipomas are standard measures for preserving cranial nerve function. Herein, we report a case of acoustic neurinoma and CPA lipoma occurring in close proximity to each other ipsilaterally. The main symptom was hearing loss without facial nerve paralysis. Therefore, facial nerve injury had to be avoided. Considering the anatomical relationships among the tumors, cranial nerves, and CPA/IAC lipoma, we performed total surgical removal of the acoustic neurinoma. We intentionally left the lipoma untreated, which enabled facial nerve preservation. This report may be a useful reference for the differential diagnosis of similar cases in the future.